Spontaneous Generation of Alkoxide Radical from Alcohols on Microdroplets Surface - Fang, Ye‐Guang; Li, Xiaoxu; Yuan, Chang; Li, Xiaojiao; Yuan, Xu; Zhang, Dongmei; Zhang, Xinxing; Zhu, Chongqin; Fang, Wei‐Hai (Angewandte Chemie International Edition, 2025)
Water microdroplets have been demonstrated to exhibit extraordinary chemical behaviors, including the abilities to accelerate chemical reactions by several orders of magnitude and to trigger reactions that cannot occur in bulk water. One of the most striking examples is the spontaneous generation of hydroxyl radical from hydroxide ions. Alcohols and alkoxide ions, being structurally similar to water and hydroxide ions, might exhibit similar behavior on microdroplets. Here, we report the spontaneous generation of alkoxide radicals from alcohols (RCH2OH) in aqueous microdroplets through quantum chemical calculations, quantum mechanical/molecular mechanical (QM/MM) molecular dynamics (MD) simulations, ab initio MD simulations, and mass spectrometry. Our results show that an electric field (EF) on the order of 10−1 V/Å and partial solvation at the air‐water interface jointly promote the dissociation of RCH2OH into RCH2O− and H3O+ ions. QM/MM MD simulations indicate that RCH2O− can be ionized to produce RCH2O⋅ radicals on the microdroplet surface. Furthermore, partial solvation and the EF collaboratively catalyze the isomerization of the RCH2O⋅ radical into a more stable tautomer, R⋅CHOH. This study highlights the molecular mechanisms underlying the widespread generation of radicals at the microdroplet surface and provides insights into the importance of fundamental alcohol chemistry in the atmosphere. We report the spontaneous generation of alkoxide radicals from alcohols (RCH2OH) in aqueous microdroplets. An electric field (~10−1 V/Å) combined with partial solvation at the air‐water interface promotes the dissociation of RCH2OH into RCH2O− and H3O+ ions. The RCH2O− ions can subsequently undergo ionization to form RCH2O⋅ radicals, which then isomerize to the more stable R⋅CHOH species.